Efficacy of herbicides on yield and economic viability of Chia (Salvia hispanica L.) in Western Rajasthan - Anuj Kumar; Moola Ram; Devi Lal Kikraliya; U.N. Shukla; R.C. Meena; P.R. Raiger (Annals of Agricultural Research, 2024)
The current field experiment was conducted at research farm of Agricultural Research Station, Mandor, Agriculture University, Jodhpur, Rajasthan during Rabi season of 2021-22 to find out the efficacy of different herbicides on chia (Salvia hispanica L.) under western Rajasthan. Application of post-emergence herbicides resulted in more seed yield of chia than application of pre-emergence herbicides and weedy check. Postemergence herbicides, bentazon 48% SL 750 g/ha recorded significantly higher seed yield followed by application of bentazon 48% SL 500 g/ha, sulfentrazon 39.6% SC 75g/ha and pendimethalin 38.7% CS 400 g/ha. Significantly higher straw yield of chia was obtained with the application of bentazon 48% SL 750 g/ha which was statistically at par with bentazon 48% SL 500 g/ha, fluazifop–p-butyl 11.1% SL 200 g/ha, sulfentrazon 39.6% SC 75 g/ha and sulfentrazon 39.6% SC 75 g/ha. The maximum increase by 61.4 per cent was recorded by weed free followed by bentazon 48% SL 750 g/ha (47.5%), bentazon 48% SL 500 g/ha (42.7%), sulfentrazon 39.6% SC 75g/ha (39.0%) and pendimethalin 38.7% CS 400 g/ha (37.6%). Among all the herbicides treatments, the significantly higher net returns and B:C ratio of chia was recorded with bentazon 48% SL 750 g/ha.